Molecular and histological validation of modified in ovulo nucellus culture based high-competency direct somatic embryogenesis and amplitude true-to-the-type plantlet recovery in Kinnow mandarin - Murugan, Theivanai; Awasthi, Om Prakash; Singh, Sanjay Kumar; Chawla, Gautam; Solanke, Amolkumar U.; Kumar, Sunil; Jha, Girish Kumar (Frontiers in Plant Science, 2023)
Kinnow (Citrus nobilis Lour. × Citrus deliciosa Ten.) needs to be genetically improved for traits such as seedlessness using biotechnological tools. Indirect somatic embryogenesis (ISE) protocols have been reported for citrus improvement. However, its use is restricted due to frequent occurrences of somaclonal variation and low recovery of plantlets. Direct somatic embryogenesis (DSE) using nucellus culture has played a significant role in apomictic fruit crops. However, its application in citrus is limited due to the injury caused to tissues during isolation. Optimization of the explant developmental stage, explant preparation method, and modification in the in vitro culture techniques can play a vital role in overcoming the limitation. The present investigation deals with a modified in ovulo nucellus culture technique after the concurrent exclusion of preexisting embryos. The ovule developmental events were examined in immature fruits at different stages of fruit growth (stages I–VII). The ovules of stage III fruits (>21–25 mm in diameter) were found appropriate for in ovulo nucellus culture. Optimized ovule size induced somatic embryos at the micropylar cut end on induction medium containing Driver and Kuniyuki Walnut (DKW) basal medium with kinetin (KIN) 5.0 mg L-1 and malt extract (ME) 1,000 mg L-1. Simultaneously, the same medium supported the maturation of somatic embryos. The matured embryos from the above medium gave robust germination with bipolar conversion on Murashige and Tucker (MT) medium + gibberellic acid (GA3) 2.0 mg L-1 + ά-naphthaleneacetic acid (NAA) 0.5 mg L-1 + spermidine 100 mg L-1 + coconut water (CW) 10% (v/v). The bipolar germinated seedlings established well upon preconditioning in a plant bio regulator (PBR)-free liquid medium under the light. Consequently, a cent percent survival of emblings was achieved on a potting medium containing cocopeat:vermiculite:perlite (2:1:1). Histological studies confirmed the single nucellus cell origin of somatic embryos by undergoing normal developmental events. Eight polymorphic Inter Simple Sequence Repeats (ISSR) markers confirmed the genetic stability of acclimatized emblings. Since the protocol can induce rapid single-cell origin of genetically stable in vitro regenerants in high frequency, it has potential for the induction of solid mutants, besides crop improvement, mass multiplication, gene editing, and virus elimination in Kinnow mandarin.